1997
DOI: 10.1002/(sici)1096-9071(199704)51:4<313::aid-jmv9>3.3.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of inapparent coinfection by hepatitis B virus in alpha interferon‐treated patients with hepatitis C virus chronic hepatitis

Abstract: The aim of the study was to investigate whether an "inapparent" coinfection by hepatitis B virus (HBV) in anti-HCV-positive chronic liver disease patients may influence interferon (IFN) response. Fourteen anti-HCV-positive, hepatitis B surface antigen (HBsAg)-negative but serum HBV-DNA-positive patients and 111 anti-HCV-positive, HBsAg-negative, and HBV-DNA-negative patients with chronic hepatitis were treated with 3 MU of recombinant alpha-2a IFN 3/week for 1.2 months. Serum HBV-DNA and HCV-RNA were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…Occult HBV infection in HCV-infected patients has been suggested as a possible co-factor, responsible for both impaired response to interferon therapy [13,18] and more severe liver disease [11,17,45,46].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Occult HBV infection in HCV-infected patients has been suggested as a possible co-factor, responsible for both impaired response to interferon therapy [13,18] and more severe liver disease [11,17,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…A reduced response to interferon therapy has been described in individuals with chronic hepatitis C and serological markers of a resolved HBV infection (HBsAg negative/anti-HBc positive), perhaps due to an inapparent HBV co-infection in these patients [18]. More recently, some authors have observed that occult HBV infection correlates with a lack of response to interferon treatment in patients with chronic hepatitis C [11,18,45]. Cacciola et al detected a virological response in 21% and 42% of HCV-positive patients who had an occult infection with HBV or not, respectively [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concomitant HCV and occult HBV co‐infection is a frequently encountered clinical entity in patients with chronic HCV infection of various frequencies (50–87%) (12, 22, 24–26). Coinfection may lead to a low rate of replication due to mutual interference between both viruses.…”
Section: Discussionmentioning
confidence: 99%